Differences in Levels of 25-hydroxyvitamin D, Human Chorionic Gonadotropin (hCG), and Progesterone in Normal Pregnancy and First Trimester Abortion - Fika Tri Anggraini; Bobby Indra Utama; Afkara Husna Firdanisa (Majalah Kedokteran Andalas, 2022)
Early pregnancy failure was defined as the failure of an intrauterine pregnancy less than 12 weeks old.This research is a comparative analytic study with  a  cross   sectional    approach. the sampling technique was consecutively taken. The normality of data was tested with the Saphiro Wilk test and data analysis with the Independent T test.Vitamin D levels were significantly higher in normal pregnancies than in the abortion group, in line with vitamin D levels as well as hCG levels and progesterone levels were significantly higher in normal pregnancies than in the abortion group. This explains the theory that vitamin D in trophoblast plays a role in regulating the production of hCG and progesterone.The conclusion in this study was that the average level of 25-hydroxyvitamin D, Human Chorionic Gonadotropin(hCG), and Progesterone were significantly different between normal pregnancies and pregnancies that had abortions in the first trimester.